2007
DOI: 10.1038/sj.onc.1210663
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factor-2 mediates transforming growth factor-β action in prostate cancer reactive stroma

Abstract: Transforming growth factor-b (TGF-b) is overexpressed at sites of wound repair and in most adenocarcinomas including prostate cancer. In stromal tissues, TGF-b regulates cell proliferation, phenotype and matrix synthesis. To address mechanisms of TGF-b action in cancerassociated reactive stroma, we developed prostate stromal cells null for TGF-b receptor II (TbRII) or engineered to express a dominant-negative Smad3 to attenuate TGF-b signaling. The differential reactive stroma (DRS) xenograft model was used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
61
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(71 citation statements)
references
References 30 publications
4
61
0
Order By: Relevance
“…In early tumor lesions, aberrant FGF-2 production and expression of its receptor (FGFR1) can alter the epithelial/stromal communication, which ensures the balance between growth and renewal of the epithelial compartment under physiological conditions (KwabiAddo et al, 2004). Moreover, FGF-2 production by both stromal and tumor cells promotes increased proliferation and metastasis formation in prostate cancer (PCa) (Cronauer et al, 1997;Giri et al, 1999;Yang et al, 2008). Thus, the FGF-2/FGFR axis is an attractive target for cancer therapy, in terms of both ligand sequestration and receptor inhibition (Smith et al, 2001;He et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In early tumor lesions, aberrant FGF-2 production and expression of its receptor (FGFR1) can alter the epithelial/stromal communication, which ensures the balance between growth and renewal of the epithelial compartment under physiological conditions (KwabiAddo et al, 2004). Moreover, FGF-2 production by both stromal and tumor cells promotes increased proliferation and metastasis formation in prostate cancer (PCa) (Cronauer et al, 1997;Giri et al, 1999;Yang et al, 2008). Thus, the FGF-2/FGFR axis is an attractive target for cancer therapy, in terms of both ligand sequestration and receptor inhibition (Smith et al, 2001;He et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The major source of FGFs is the stromal compartment in the normal prostate. A balanced interaction between stromal and epithelial cells through FGFs, which act as paracrine growth factors for epithelial cells, is crucial for normal development and growth of prostate epithelium (Tuxhorn et al 2002, Ayala et al 2003, Yang et al 2008. FGF-2 supports proliferation, migration and invasion in human prostate cancer cellular models (Wesley et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the volume of reactive stroma relative to cancer is predictive of the rate of cancer progression in several tumor types (8)(9)(10)(11)(12)(13)(14)(15). Furthermore, in vivo modeling has shown that reactive stroma is tumor-promoting (16)(17)(18)(19). The myofibroblast is the principal cell type in reactive stroma, and transforming growth factor beta 1 (TGF-β1) is a potent inducer of myofibroblast differentiation (3,20).…”
mentioning
confidence: 99%